Sedentary behavior as a risk factor for cognitive decline: A focus on the influence of glycemic control in brain health - Wheeler, Michael J; Dempsey, Paddy C; Grace, Megan S; Ellis, Kathryn A; Gardiner, Paul A; Green, Daniel J; Dunstan, David W (Alzheimer's & dementia : translational research & clinical interventions, 2017)
Abstract Cognitive decline leading to dementia represents a global health burden. In the absence of targeted pharmacotherapy, lifestyle approaches remain the best option for slowing the onset of dementia. However, older adults spend very little time doing moderate to vigorous exercise and spend most of time in sedentary behavior. Sedentary behavior has been linked to poor glycemic control and increased risk of all-cause mortality. Here, we explore a potential link between sedentary behavior and brain health. We highlight the role of glycemic control in maintaining brain function and suggest that reducing and replacing sedentary behavior with intermittent light-intensity physical activity may protect against cognitive decline by reducing glycemic variability. Given that older adults find it difficult to achieve current exercise recommendations, an additional practical strategy may be to reduce and replace sedentary behavior with intermittent light-intensity physical activity. However, more research is needed to understand the impact of poor glycemic control on brain function and whether practical interventions aimed at reducing sedentary behavior can help slow cognitive decline.